2021
DOI: 10.1111/jocs.15552
|View full text |Cite
|
Sign up to set email alerts
|

Thoracotomy versus sternotomy? The effect of surgical approach on outcomes after left ventricular assist device implantation: A review of the literature and meta‐analysis

Abstract: Background and aim: Thoracotomy approaches to left ventricular assist device (LVAD) implantation may reduce surgical morbidity and, through preservation of the pericardial restraint over the right heart, may reduce the incidence of right ventricular failure (RVF).Methods: A meta-analysis of all original studies describing the effect of the surgical approach on postoperative outcomes after LVAD implantation was performed. Postoperative outcomes analyzed.Results: Thirteen studies were included with 692 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Recent meta-analyses of LVAD implantation via thoracotomy approach suggest that the thoracotomy approach was associated with a reduced incidence of RVF, bleeding, hospital length of stay (LOS), and mortality [1 ▪▪ ,2 ▪▪ ]. No difference in stroke rates was noted.…”
Section: Recent Findingsmentioning
confidence: 99%
“…Recent meta-analyses of LVAD implantation via thoracotomy approach suggest that the thoracotomy approach was associated with a reduced incidence of RVF, bleeding, hospital length of stay (LOS), and mortality [1 ▪▪ ,2 ▪▪ ]. No difference in stroke rates was noted.…”
Section: Recent Findingsmentioning
confidence: 99%
“…Multiple single-center studies and two meta-analyses have suggested a reduction in RVF after LVAD implantation by a thoracotomy approach, and it has been similarly theorized that preservation of the pericardial restraint around the RV allows for maintenance of RV geometry and function. 20,21 Reductions in bleeding and transfusion requirements with a thoracotomy approach demonstrated in these studies likely also contribute to improved RV function as the myocardial injury incurred from acute stretch after blood product transfusions is likely amplified in the absence of the pericardial restraint around the RV. group as well as demonstrated by lower right ventricular stroke work index and a trend to higher CVP.…”
mentioning
confidence: 93%
“…Minithoracotomy approaches to left ventricular assist device (LVAD) placement have demonstrated significant reductions in bleeding complications, length of stay, and mortality 4 . Most interestingly, reductions in right ventricular failure (RVF) were noted, and it was hypothesized that preserving the pericardial restraint around the right heart during minithoractomy approaches may explain these findings 4,5 .…”
mentioning
confidence: 99%
“…4 Most interestingly, reductions in right ventricular failure (RVF) were noted, and it was hypothesized that preserving the pericardial restraint around the right heart during minithoractomy approaches may explain these findings. 4,5 Reductions in RV function after sternotomy mitral valve replacement and coronary bypass grafting have been demonstrated, with the decline noted at the time of pericardial incision, and these changes are similarly not seen after nonsterntomy approaches to these procedures in which the pericardial restraint over the right heart is preserved. [6][7][8][9][10][11] In line with this, a recent study has demonstrated greater reductions in echocardiographic markers of RV function after FS AVR compared to MS AVR, but no difference in clinical outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation